CO-VIEW (Collaborative Vision and Exploration Workbench): software and manual - Haggith, M.; Purnomo, H.; Zacharias, T.; Yulianto, E.; Prabhu, Ravi; Theodore, Y.; Muetzelfeldt, R.; Yuliani, L.; Yasmi, Yurdi; Suharyanto, G.; Kusnadi, R. (Center for International Forestry Research, 2002)
Co-View is a tool to help facilitators of natural resource management and stakeholders to articulate and explore a shared vision of the future and to develop strategies to achieve it. One promising approach for coping with change is by generating a shared vision of the future through facilitated participatory visioning processes. Visioning has become widely accepted as an important tool for empowering local communities to gain confidence over their future. Co-View includes: 1. A practical guide to facilitating a participatory visioning process; 2. Future Scenario, Scenarios as a Tool for Adaptive Forest Management; 3. a simply written, illustrated guide to participatory modelling; 4. 'The Bridge', a computer-based tool for expressing a vision and converting it into the basis of a simulation model; 5. 'The Power to Change!” game, a team game for using a model to explore various future scenarios. (Simile software required).